الإضافة ودلالتها في كتاب الصلاة من صحيح البخاري : دراسة تحليلية - Norliza binti Erhan (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
This research concentrates on the study of the annexation (Al-Idafah) and its meaning in the linguistics and grammatical field. The style of annexation (Al-Ỉdafah) has the tendency to convey many meanings through its different rules of usage. This research examines the text book of Al-Bukhary (Sahih Al-Bukhari) to analyze annexation (Al-Idafah) in the Arabic sentence structure. The researcher uses the ideas of classical and modern grammarians’ studies on annexation (Al-Idafah) and then tries to analyze the annexation (Al-Idafah) pattern in the prayer’s chapter of Al-Bukhary’s book (Sahih Al-Bukhari) to see whether it is consistent with the rules established by modern grammarians. The researcher found that the Sunna texts (Al-Hadith al-Nabawi) are a fertile field for applying linguistics and grammatical studies, especially in the area of annexation (Al-Ỉdafah).